BENTUK DISFEMISME DALAM SINIAR “KOMPLEKS KIKY” EPISODE PENGAKUAN KAESANG SOAL DINASTI POLITIK - Kusuma, Indah Dewi; Siagian, Irwan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to describe the form of dysphemism in the Kiky Kompleks Podcast Episode Pengakuan Kaesang Soal Dinasti Politik through the study of the theory of Wijana & Rohmadi. The research method uses a qualitative descriptive with data collection of SBLC techniques and recorded techniques. The data in this study used data in the form of discourse manipulation in the Kiky Kompleks Podcast of Pengakuan Kaesang Soal Dinasti Politik that has elements of the theory of Wijana and Rohmadi and the theories of Firmansyah, Ristiyani, and Roysa. The object of the study is Kiky Saputri, Pak RT, House Assistant, and resource person (Kaesang Pangarep). Based on data analysis, the researchers found that dysphemism in the Kiky Kompleks Podcast of Pengakuan Kaesang Soal Dinasti Politik has three forms: namely rudeness or swearing in the form of words, rudeness or swearing in the form of phrases, and rudeness or insults in the form of clauses.